Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1971
DOI: 10.1111/j.1467-8489.1971.tb00073.x
|View full text |Cite
|
Sign up to set email alerts
|

Risk, Utility and Stocking Rate*

Abstract: A simple utility-based model of risky wool production is presented. Evaluation of the model indicates the effect on optimal stocking rate of changes in the degree of risk aversion, farm area, variable cost, fixed cost, wool cut, wool price, variance of wool price, climatic variability and tax rate. It is shown that the utility hypothesis implies a lower optimal stacking rate than does expected profit maximization and hence implies a discrepancy between private and public optima1 resource use which it is sugges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1972
1972
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…That both stocking rates and the use of inputs may be modified by considerations of financia! risk has been shown for sheep farming in Australia (MacArthur and Dillon, 1971;Anderson and Griffiths, 1981). However, it is difficult to derive a function which describes the willingness of livestock producers to accept lower expected incomes in exchange for a reduction in income variability.…”
Section: Quantifying Riskmentioning
confidence: 99%
“…That both stocking rates and the use of inputs may be modified by considerations of financia! risk has been shown for sheep farming in Australia (MacArthur and Dillon, 1971;Anderson and Griffiths, 1981). However, it is difficult to derive a function which describes the willingness of livestock producers to accept lower expected incomes in exchange for a reduction in income variability.…”
Section: Quantifying Riskmentioning
confidence: 99%
“…The holding of large numbers of unproductive animals and overgrazing of public lands are often seen as risk-reducing devices. Conversely, Macarthur and Dillon (1971) illustrated how risk-adverse behaviour by private ranchers leads to understocking and underinvestment relative to socially optimal (i.e. risk-neutral) levels.…”
Section: Riskmentioning
confidence: 98%
“…However, alternative attitudes to risk by graziers are likely to influence their stocking decisions (McArthur and Dillon 1971). For instance, income uncertainty due to climatic factors may force risk averse graziers to adopt lighter stocking rates so as to reduce the impact of drought, while wool price uncertainty may encourage the risk averse grazier to increase stocking rates to extenuate the impact of lower wool prices.…”
Section: Risk Attitudesmentioning
confidence: 99%
“…Mills et al (1989), however, found that land condition did not differ significantly between the largest and smallest properties. Previously, McArthur and Dillon (1971) used a static utility model to show that increases in property size led to a fall in optimal stocking rates for the risk averse grazier. However, optimal stocking rates were not influenced by property size given a risk neutral attitude; that is, where maximisation of profits was the goal.…”
Section: Analysis Of Rangeland Degradation 135mentioning
confidence: 99%